A2BC-type meso-imidazolylporphyrins – New class of prospective polyfunctional molecules. (November 2022) - Korobkov, Stepan M.; Birin, Kirill P.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu.
Abstract: A convenient synthetic strategy for the efficient preparation of new functionalized low-symmetry A2 BC-type porphyrins bearing meso -areneimidazolyl fragment is developed. The reactivity of the key precursors, namely 5-bromo-15-imidazolylporphyrins, in C–C-coupling reactions was evaluated providing access to target functional derivatives. Two types of electron-withdrawing groups, namely cyano- and phenylcarboxy-ones, were introduced to the meso -position, opposite to the heterocyclic substituent. It allowed preparation of prospective push-pull derivatives along with the introduction of latent anchoring groups to the macrocycle. The peculiarities of the mutual intramolecular dynamic processes in the prepared compounds were revealed and investigated by means of variable-temperature NMR. DFT calculations of the structure, molecular orbitals and rotation activation barriers were performed, that revealed the conformational dependence of the orbitals localization. Altogether the obtained results form the basis for the rational design of highly unsymmetrical and polarized porphyrin derivatives with tunable properties. Highlights: Strategy for the elaboration of new A2 BC-type porphyrins is developed. 5-bromo-15-imidazolylporphyrins - convenient semiproducts for the preparation of functional low-symmetry derivatives. Reactivity of 5-bromo-15-imidazolylporphyrins in C–C-cross-coupling reactions is evaluated. Mutual dynamic processes of the molecular fragments are investigated by VT-NMR. Conformational dependence of the energy levels and localization of molecular orbitals is revealed.